The Mesothelial Cell as a Non-Thrombogenic Surface - Nicholson, L J; Clarke, J M F; Pittilo, R M; Machin, S J; Woolf, N (Thrombosis and Haemostasis, 1984)
A technique for harvesting mesothelial cells is described. This entails collagenase digestion of omentum after which the cells can be cultured. The technique has been developed using the rat, but has also been successfully applied to human tissue. Cultured rat mesothelial cells obtained in this way have been examined by scanning electron microscopy. Rat mesothelial cells grown on plastic film have been exposed to blood in an in vitro system using a Baumgartner chamber and have been demonstrated to support blood flow. No adhering platelets were observed on the mesothelial cell surface. Fibroblasts similarily exposed to blood as a control were washed off the plastic.
Keywords: Mesothelial cell; Cell culture; Scanning electron microscopy; Platelets; Artificial circulation; Vascular prosthesis